Seasonal variations in somereproductive parameters of Dorper Rams in Hungary - Budai, Csilla; Oláh, János; Egerszegi, István; Jávor, András; Kovacs, András (Acta Agraria Debreceniensis, 2013)
The purpose of the present study was to test the hypothesis that season has an affect on semen quality and scrotal circumference of Dorper rams. The experiment was carried out with six Dorper rams aged between 15 and 18 month. Semen samples were collected with artificial vagina and volume, concentration (x 109/ml), total sperm number/ejaculate (x 109), mass motility (0–5), progressive motility (%), scrotal circumference (cm) was observed. Significant differences (P